Multi-site fungicides associated with DMIs and QoIs: a new strategy to control asian soybean rust - Ponce Ortiz, Roberto Baruch (2015)
Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi, since it was first reported in Brazil, has been the subject of studies regarding the use of fungicides to its control. However, due to the indiscriminate use of this products, especially from the DMIs ("demethylation inhibitors") and QoIs ("Quinone outside inhibitor") groups, also known respectively as triazoles and strobilurins, resistance reports are increasingly common nowadays. In order to study new strategies for chemical control of ASR, experiments were conducted in laboratory, greenhouse and field to evaluate the effect of fungicides belonging to the DMIs and QoIs groups associated with multi-site fungicides. Experiments were carried out at laboratory and greenhouse in order to study the systemic and translaminar effect of triazoles (Epoxiconazole, Cyproconazole, Prothioconazole, Flutriafol and Tebuconazole) and Strobilurins (Pyraclostrobin and Trifloxystrobin), and for the experiment in greenhouse were mixed these lasts with multi-site fungicides like (Mancozeb and Chlorothalonil). Based on the results obtained in the laboratory and greenhouse, field trial experiments were conducted to evaluate the effect of fungicides compounded with triazole like Epoxiconazole and Cyproconazole, and strobilurins like Pyraclostrobin and Azoxystrobin with Mancozeb, Metiram and Chlorothalonil. ASR was assessed by the severity using a diagrammatic scale and the data were integrated to calculate the area under the disease progress curve (AUDPC). Besides the evaluation of disease, it was determined grain yield (kg/ha) for each plot. The bioassay conducted in the laboratory and greenhouse showed that the fungicide treatments obtained a minimum efficacy of 92 % against ASR, compared to the control. The field trials showed that all combinations of fungicides used were effective to control ASR and promoted greater yield gain compared to the control. Analyzing the effectiveness to control ASR in the lower, medium and upper part of the canopy, showed that application of Expoxiconazole with Pyraclostrobin, and Cyproconazole with Azoxystrobin reduced ASR (lower, medium and upper) and leaf fall (%), and increased yield gain (kg/ha). It was observed that the incidence of the ASR differed between the canopy parts. The severity increased from lower to the upper part. It was evidenced in this work, that the application of DMI, QoI and multi-site fungicides in association promoted effectively the disease reduction, increased yield and avoided the leaf fall. The use of commercial formulation fungicides with high risk of resistance (DMI and QoI) combined to low risk ones (multi-site) could be a new strategy for the management of the ASR at short and long term. Furthermore, due to the residual effect and protective of multi-site fungicides like Mancozeb, Chlorothalonil and Metiram, can promote higher longevity of DMI and QoI molecules and reduce the number of application of systemic fungicides.